2022
DOI: 10.3389/frsc.2022.920722
|View full text |Cite
|
Sign up to set email alerts
|

Consumer food demand in Japan before and after the beginning of COVID-19: AIDS analysis using home scan data

Abstract: COVID-19 had an impact not only on human health but also on consumers' food consumption. Employing the Almost Ideal Demand System (AIDS), this study analyzes whether consumers change their demand for food between 2019 and 2020 in Japan, where the legal action was not implemented to restrict consumer behavior. Using the home scan data, 25 food items, including eating out and delivery, were analyzed to see the impact of COVID-19. Results show that the increase in shares of expenditure is mainly related to consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, we rule out the notion that meat acts as a substitute for seafood in this study. This is supported by Ito et al [14], who demonstrated, through their analysis conducted in 2020, that meat did not substitute for seafood. Table 2 shows that the percentage of people who did not buy seafood during the COVID-19 era was much higher for high-end seafood compared to popular seafood.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, we rule out the notion that meat acts as a substitute for seafood in this study. This is supported by Ito et al [14], who demonstrated, through their analysis conducted in 2020, that meat did not substitute for seafood. Table 2 shows that the percentage of people who did not buy seafood during the COVID-19 era was much higher for high-end seafood compared to popular seafood.…”
Section: Methodsmentioning
confidence: 64%
“…They anticipate that this rise in EC sales may be linked to a decreased expenditure for dining out. Ito et al [14] examined food demand in the Tokyo metropolitan area between 2019 and 2020 using home scan data. They observed that the rise in expenditure on food consumption in 2020 was predominantly associated with home consumption, whereas spending on dining out decreased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Vargas-Lopez et al (2022) analyze expenditure and price elasticities of food waste in Mexico. Ito et al (2022) use the AIDS to examine expenditure and price elasticities of food in Japan. However, both of them just compare the separate estimation results before and after the COVID-19 without statistical tests of changes in elasticities.…”
Section: Introductionmentioning
confidence: 99%